Approaches to Effective Management in Reducing Plastic Waste in Malaysia from the Socio-Legal Aspect - Kamaruddin, Hanim; Jasri, Nur Insyirah Bt; Halid, Munirah binti Mohamed; Mohd, Nur Wafaa Azreen binti; Hashim, Nur Hasyazira Binti; Nawawi, Nur Najwa Athirah bt Mohamed; Puthucheary, Sahain Nada (The journal of contemporary issues in business and government, 2021)
Plastic waste pollution is a major problem in Malaysia as the country ranks among the top ten countries with mismanaged plastic waste in the world. Malaysia has produced significant amount of plastic waste where most are washed into the oceans, dumped at landfills, burnt, and a fraction being recycled. This situation continuously affects human health and environment especially in marine waters. Existing waste management practices lack in handling large amount of plastic waste from household and businesses as there is no uniform approach within Malaysia to address the use of plastic waste. This paper reviews and analyses existing laws and social practice in relation to reducing plastic waste in Malaysia. It concludes that initiatives by the Malaysian government to reduce plastic waste is still within preliminary stages, and substantive legal approach remains absent.